The use of supplementary materials in EFL classes: A comparative analysis of public and private high schools - Romero Nivelo, Ana Lucía. (2013)
The use of supplementary materials in the EFL classes is a language teaching resource that fairly matches the new methodologies and today`s necessities highly recommended in language teaching and learning. The purpose of this study was to find out whether or not teachers use supplementary materials in the classrooms and if they helped to the teaching- learning process. This research was developed at a private and public high school in the Cañar province, first, second and third senior year were observed in each high school. A Qualitative and Quantitative analysis was conducted in order to determine if the teachers used supplementary materials, and if they did, how pertinent, appropriate and qualified they were. As the main conclusion it was determined that there were differences in the use of supplementary materials between public and private high schools. At the public school there was almost a total absence of materials and the whiteboard was the most frequently used. While, at the private schools teachers used efficient supplementary materials which resulted in an effective language teaching- learning process and increased student`s motivation.